Complications in the post-anaesthesia recovery room - Ismail, Wan Azzlan Wan (1995)
A prospective survey was conducted over a threemonths period in all post-surgical patients entering the post-anaesthesia recovery room ( PARR ) at a university teaching hospital, while excluding those patients who had local anaesthesia or those who bypassed the recovery room to be transferred directly to the intensive care unit { ICU ). To identify and quantitate complications occuring in the PARR, a standardized collection form with predefined criteria was used. A total of 1304 patients were presented to the recovery room. The majority of them underwent general anaesthesia ( 85.28% ). In 110 ( 8.43% ) of the patients, some form of PARR complications were noted. With respect to type of anaesthesia, the PARR complications within groups of patients receiving general anaesthesia ( GA ) only, GA combined with central blockade and regional anaesthesia only were 8.36%, 10.0% and 7.84% respectively. Quite surprisingly, 11.1% of elective and only 6% of emergency patients had PARR complications. ASA physical status appeared to be an important factor in determining the incidence of overall PARR complications, with higher ASA status showing more complications. Patients who had anaesthesia less than 2 hours presented with the least incidence of 6.76% whereas those who underwent anaesthesia more than 5 hours had over 40% complication rate. Even though there were higher incidence of PARR complications amongst the orthopaedic, obstetric, gynaecological and abdominal procedure patients corresponding to the number of cases done, urologic patients developed the highest incidence of adverse outcome among themselves ( 25.58% ). There was no complication noted in the neurosurgical patients as those with high ASA status were directly admitted to ICU. out of the PARR complications observed, 3.91% were referable to the central nervous system, 3.07% to gastrointestinal tract, 2.61% to cardiovascular system, a mere 0.31% to respiratory system and 1.3% to others. Pain ( 2.99% ), nausea and vomiting ( 2.45% ), and tachycardia ( 1.38% } were the most frequently encountered PARR complications. The more dangerous complications such as hypotension, hypertension, myocardial ischaemia and respiratory compromise do This is most likely due to still occur, but at a lower rate. different anaesthetic practice, reporting criteria and patient population. In conclusion, the immediate post-anaesthesia period in the recovery room remain as a time of great potential danger to patients emerging from anaesthesia and a source of patient morbidity.